Analisis Kinerja Lembaga Zakat Infaq dan Shodaqoh Dengan Metode Balanced Scorecard (Studi Kasus pada Lazis Al-Ihsan Jawa Tengah Cabang Solo Raya) - Lulu Syifa Pratama (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to analyze the performance of LAZIS Al-Ihsan, Central Java, Solo Raya Branch. With a qualitative approach, the data in this study were obtained by distributing questionnaires to public relations and volunteers of LAZIS Al-Ihsan, the Solo Raya branch. The results of this study indicate that from a financial perspective, LAZIS Al-Ihsan has sufficient growth, which is 44% from the previous year. Then in LAZIS Al-Ihsan’s internal business perspective, it has been running operational activities in accordance with sharia principles, and finally in the perspective of growth and learning, LAZIS Al-Ihsan already has a training program to improve the skills of volunteers so they can work professionally in their fields.Keywords: balanced socrecard, LAZIS, performance